Correction: Scalable synthesis and structural characterization of reversible KLK6 inhibitors. Issue 44 (10th October 2022) - Baumann, Andreas; Isak, Daniel; Lohbeck, Jasmin; Jagtap, Pravin Kumar Ankush; Hennig, Janosch; Miller, Aubry K.
Abstract : Correction for 'Scalable synthesis and structural characterization of reversible KLK6 inhibitors' by Andreas Baumann et al., RSC Adv., 2022, 12, 26989–26993, ; https://doi.org/10.1039/D2RA04670A .